2006
DOI: 10.1016/j.jtbi.2005.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Friendship, cliquishness, and the emergence of cooperation

Abstract: The evolution of cooperation is a central problem in biology and the social sciences. While theoretical work using the iterated prisoner's dilemma (IPD) has shown that cooperation among non-kin can be sustained among reciprocal strategies (i.e. tit-for-tat), these results are sensitive to errors in strategy execution, cyclical invasions by free riders, and the specific ecology of strategies. Moreover, the IPD assumes that a strategy's probability of playing the PD game with other individuals is independent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 43 publications
2
87
1
Order By: Relevance
“…Our results are in line with previous models that have incorporated optional interactions or partner choice allowing cooperative individuals to refuse non-beneficial interactions [27][28][29][30][31]. The most notable work is by [31], where, similarly to our study, the coevolution of choosiness and cooperation was examined.…”
Section: Best Strategy Solutions (Reached By Evolution)supporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in line with previous models that have incorporated optional interactions or partner choice allowing cooperative individuals to refuse non-beneficial interactions [27][28][29][30][31]. The most notable work is by [31], where, similarly to our study, the coevolution of choosiness and cooperation was examined.…”
Section: Best Strategy Solutions (Reached By Evolution)supporting
confidence: 91%
“…However, even though previous work has explored various forms of optional interactions and partner choice, particularly in the theory of the evolution of cooperation [25][26][27][28][29][30][31][32], trade-offs arising from sequential search problems have not been studied. In this paper, we address this issue by embedding a mutual choice sequential search problem to an evolutionary game-theoretical framework, and look for decisions that are favored by evolution.…”
Section: Introductionmentioning
confidence: 99%
“…As we will see below, coalitions can serve different functions (van Schaik et al, 2006); they can be observed among different sex and age classes (reviewed in Chapais, 1995); they can involve kin (e.g., Riss & Goodall, 1977;Chagnon & Bugos, 1979;Wahaj et al, 2004), non-kin (e.g., Vigilant et al, 2001;Langergraber et al, 2007;Schülke et al, 2010), and friends or acquaintances (Hruschka & Henrich, 2006;Hruschka, 2010). As this brief review makes clear, coalitionary patterns are varied, and understanding this diversity would be greatly enhanced by formal modelling that would allow us to identify the general conditions under which coalition formation is expected to evolve, characterize the degree of variability expected, and predict when coalitions should, and should not, occur.…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
“…Third, the theory of dynamic linking and network formation focuses on dyadic or polyadic games played by individuals in which the outcomes of previous interactions determine who interacts with whom in the future (Skyrms & Pemantle, 2000;Pemantle & Skyrms, 2004a, b;Hruschka & Henrich, 2006;Pacheco et al, 2006Pacheco et al, , 2008Santos et al, 2006;Gavrilets et al, 2008;Aktipis, 2011). We discuss one application of this theory below.…”
Section: General Theoretical Perspectivesmentioning
confidence: 99%
“…Low-value social partners are potentially profitable targets of exploitation, given that they have few benefits to withhold in the future. The primary psychopathy continuum may correspond to a relative willingness to strategically exploit or invest in others based upon their appraised utility-which might motivate defection if partners are deemed of low-value, including if future interactions are unlikely, but which should motivate cooperation in interactions with valuable, long-term partners [34]. This stands in stark contrast to simplistic rules such as 'always defect' or 'defect whenever possible', the predominant strategies assumed in the psychopathy literature.…”
Section: Introductionmentioning
confidence: 99%